2021
DOI: 10.21203/rs.3.rs-246296/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional and structural brain connectivity in congenital deafness

Abstract: Several studies have been carried out to verify neural plasticity and the language process in deaf individuals. However, further investigations regarding the intrinsic brain organization on functional and structural neural networks derived from congenital deafness is still an open question. The objective of this study was to investigate the main differences in brain organization manifested in deaf individuals, concerning the resting-state functional patterns, and white matter structuring. Functional and diffus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Efficient task performance was associated with stronger modularity in the task-negative DMN in terms of higher within-module connectivity in the DMN and lower between-module connectivity between the DMN and the task-relevant neural networks (Gonzalez-Castillo and Bandettini, 2017). It has been suggested that the DAN and the FPN, two task-critical networks supporting the egocentric task, show stronger functional and structural connectivity with the DMN in early deaf people (Dell Ducas et al, 2021;Li et al, 2022). Moreover, the increased inter-network connectivity between the task-irrelevant DMN and the task-relevant DAN and FPN was associated with impaired egocentric performance in congenitally deaf people (Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Efficient task performance was associated with stronger modularity in the task-negative DMN in terms of higher within-module connectivity in the DMN and lower between-module connectivity between the DMN and the task-relevant neural networks (Gonzalez-Castillo and Bandettini, 2017). It has been suggested that the DAN and the FPN, two task-critical networks supporting the egocentric task, show stronger functional and structural connectivity with the DMN in early deaf people (Dell Ducas et al, 2021;Li et al, 2022). Moreover, the increased inter-network connectivity between the task-irrelevant DMN and the task-relevant DAN and FPN was associated with impaired egocentric performance in congenitally deaf people (Li et al, 2022).…”
Section: Discussionmentioning
confidence: 99%